Science, Common Sense, and Criminal Law Reform - Hall, Jerome (1964)
Professor Hall advocates a reappraisal of the current trend in criminal law of substituting expert psychiatric testimony for common-sense determinations of insanity based on the long experience of the criminal-law tradition. Holding that the average layman is as competent to recognize extreme mental illness as the psychiatric expert, the author discusses the doctrine of the irresistible impulse and submits that the current departures from the M'Naghten rule tend to substitute the ideology of a particular group of psychiatrists for the principle of moral responsibility. Professor Hall suggests that realistic reform cannot be achieved without considering the moral life and its connection with the criminal law